Negotiating Religion and Development Identity Construction and Contention in Bolivia - Arnhild Leer-Helgesen (2019)
This book argues that relationships between religion and development in faith-based development work are constructed through repeated processes of negotiation. Rather than being a neat and tidy relationship, faith-based development work is complex and multifaceted: an ongoing series of negotiations between theological interpretations and theories of human development; between identities as professional practitioners and as believers; between different religious traditions at local, regional and international levels; and between institutional structures and individual agency.